2013
DOI: 10.1111/bjh.12391
|View full text |Cite
|
Sign up to set email alerts
|

The association between tricuspid regurgitation velocity and 5‐year survival in a North West London population of patients with sickle cell disease in the United Kingdom

Abstract: SummaryRaised tricuspid regurgitant velocity (TRV) occurs in approximately 30% of adults with sickle cell disease (SCD), and has been shown to be an independent risk factor for death. TRV was assessed in 164 SCD patients who were subsequently followed up for survival. Raised pulmonary pressures were defined as a TRV jet ! 2Á5 m/s on echocardiography. Elevated TRV was present in 29Á1% of patients and it was associated with increased age and left atrial diameter. There were 15 deaths (9Á1%) over a median of 68Á1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 30 publications
1
19
1
Order By: Relevance
“…Forty full‐text articles were assessed for eligibility (Figure 1). Fifteen (8 RHC and 7 echocardiography) studies were included in the meta‐analysis 2, 3, 4, 5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. The characteristics of the included studies are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty full‐text articles were assessed for eligibility (Figure 1). Fifteen (8 RHC and 7 echocardiography) studies were included in the meta‐analysis 2, 3, 4, 5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. The characteristics of the included studies are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Studies included in this analysis are Valerio et al,10 Heresi et al,11 Kovacs et al,5 Suzuki et al,12 Maron et al,3 Takahashi et al,13 Douschan et al,4 Assad et al,2 Abramson et al,14 Kjaergaard et al,15 Shalaby et al,16 Lam et al,17 Damy et al,18 Cabrita et al,19 and Choudhary et al 20. CI indicates confidence interval; M‐H, Mantel‐Haenszel; RHC, right heart catheterization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diastolic dysfunction is an independent risk factor for early mortality in SCD(7,8). In our patients, diastolic dysfunction was associated with LA dilation, which was the most severely and disproportionately enlarged heart chamber.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the degree of PH, which is often mild in individuals with SCD, does not readily explain the full extent of cardiac morbidity and frequency of early mortality in SCD(7). Nevertheless, TRV, pulmonary pressure and diastolic dysfunction are clearly associated with increased mortality and sudden death in SCD(2,7,8). The causes of cardiac-related mortality in the absence of apparently clinically significant PH have remained unclear.…”
Section: Introductionmentioning
confidence: 99%